INVESTIGACIONES SOBRE LISOZIMA II EFECTO DE LA LISOZIMA DE LA LECHE DE BURRA SOBRE LA ACCION BACTERIOLITICA DE LOS SUEROS - HUERTA, LAURA; CASTANEDA AGULLO, M (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1979)
Study of tranverse and longitudinal serial sections and the application of dissociating techniques disclose that the innermost layer of the esophagus of the American leopard frog is pseudostratified, ciliated columnar epithelium, composed of 2 kinds of ce
ANAL CHEM
Keywords: INVESTIGACIONES, LISOZIMA II, EFECTO DE LA LISOZIMA, LECHE DE BURRA, ACCION BACTERIOLITICA, SUEROS; CIENCIAS DE LA VIDA; MICROBIOLOGIA; PROCESOS MICROBIANOS